Penerapan Model Pembelajaran SSVI (Somatis Auditori Visual Intelektual) Untuk Meningkatkan Keaktifan Belajar Siswa Dalam Pembelajaran Ipa Kelas III SD Negeri 1 Lebengjumuk Tahun 2015/ 2016 - Suratman, Nurul Hasanah; , Drs. Muhroji, S. E., M. Si., M. Pd (2015)
This research aims to enhance the activity of the third grade students of SD Negeri 1 Lebengjumuk year 2015/2016 in learning science through the application of learning models SAVI (Somatic Visual Auditory Intellectual). This type of research is the Classroom Action Research (PTK). This research subject is the teacher (researcher) and third-grade students who totaled 25 people. The technique of collecting data using interviews, observation, documentation, and testing. While the captured data includes data activeness of student learning and learning outcomes data IPA. The validity of the data and instruments using triangulation. Data analysis techniques wearing Interactive Analysis Model consisting of three components: data reduction, data presentation and conclusion / verification data. Results of pre-cycle observation showed activeness of students in science learning 58.33%, while students who achieve KKM or get a ≥ 62 No 41.66%. Each cycle consists of planning, implementation, observation, and reflection. The results of the first cycle study, 72% of students' learning activeness and learning outcomes of students who reached KKM 64%. While Cycle II students' learning activeness increased to 96%. Learning outcomes of students who reached the KKM also increased to 88%. Judging from the results, then the application of Learning Model SAVI (Somatic Visual Auditory Intellectual) may enhance the activity of students in science teaching third grade of SD Negeri 1 Lebengjumuk year 2015/2016.